2001
DOI: 10.1007/s002030100319
|View full text |Cite
|
Sign up to set email alerts
|

A novel denitrifying bacterial isolate that degrades trimethylamine both aerobically and anaerobically via two different pathways

Abstract: The aerobic and anaerobic degradation of trimethylamine by a newly isolated denitrifying bacterium from an enrichment culture with trimethylamine inoculated with activated sludge was studied. Based on 16S rDNA analysis, this strain was identified as a Paracoccus sp. The isolate, strain T231, aerobically degraded trimethylamine, dimethylamine and methylamine and released a stoichiometric amount of ammonium ion into the culture fluid as a metabolic product, indicating that these methylated amines were completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 32 publications
2
59
1
Order By: Relevance
“…To the best of our knowledge, this is the first report of a bacterial strain that can grow with N,O-DMHA as the sole source of C, N, and energy. Other members of the genus are able to degrade related compounds, such as trimethylamine, dimethylamine, and methylamine (25), as well as halomethanes, methyl sulfates, and methylated phosphates (27). Although it was assumed that N,O-DMHA would be degraded to hydroxylamine, no growth of WDL6 or one of the other strains was observed on hydroxylamine as an N source in the presence of methanol as a C source (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of a bacterial strain that can grow with N,O-DMHA as the sole source of C, N, and energy. Other members of the genus are able to degrade related compounds, such as trimethylamine, dimethylamine, and methylamine (25), as well as halomethanes, methyl sulfates, and methylated phosphates (27). Although it was assumed that N,O-DMHA would be degraded to hydroxylamine, no growth of WDL6 or one of the other strains was observed on hydroxylamine as an N source in the presence of methanol as a C source (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prokaryotes can convert TMAO back to trimethylamine (Zhang et al, 1999). Alternatively, dehydrogenase enzymes from at least some bacteria can convert trimethylamine into dimethylamine (Kim et al, 2001;Shi et al, 2005) with subsequent conversions to methylamine and ammonia (Kim et al, 2001), although whether this ability is shared by commensal bacteria is unknown.…”
Section: Trimethylaminementioning
confidence: 99%
“…It can be emitted from fish-meal manufacturing plants (Kim et al, 2001) and swine waste storage pits (Ho et al, 2008). Besides its malodorous property and chronic harmful effects on humans, TMA can also inhibit the synthesis of macromolecules and has teratogenic effects on animal embryos (Guest and Varma, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental slope was 53.1% of the theoretical slope, indicating that about 53.1% of TMA carbon was completely mineralized and that 46.9% remained as biomass, intermediates, or other forms. Kim et al (2001) reported that TMA could initially oxidize to dimethylamine by way of TMA N-oxide, then to methylamine by enzymes during biodegradation, and then finally oxidized to formaldehyde and NH 3 under aerobic conditions. However, only one intermediate, dimethylamine, was detected in the gas phase in the present study (Fig.…”
mentioning
confidence: 99%